Programming skills in social groupwork - Ross, Sue; Thorpe, Andy (Groupwork, 2020)
This article offers groupworkers a way of tackling the tasks of drawing up a programme of work in a group. It uses groupwork theories about group process and leadership to help the group leader think about how best to use the group sessions to bring about changes in the group members. The technique of linear programming, which it describes, gives a framework for thinking about, and working on and evaluating, the work of a group within individual sessions, over a whole group session and over a total programme of groupwork. It is based on practice - the authors’ and other groupworkers’ - who have used it and found it helpful in looking at the complex issues involved in working out group programmes. It is not offered as a prescriptive model in groupwork, but rather as a way of developing links between theory and method which should lead to better more effective groupwork. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication. Abstracts are word-for-word transcriptions of the original abstracts without any attempt to update terminology.